Role of clopidogrel in addition to aspirin in the prevention of recurrent ischaemic events in acute coronary syndrome with ST-segment elevation - Patra, Vasavi; Ulchala, Victor Emmanuel (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Studies regarding the efficacy of Aspirin alone versus combination of Aspirin and Clopidogrel in patients with Unstable Angina are many. But, studies on the comparative role of Aspirin alone versus Aspirin plus Clopidogrel in the background of Acute Coronary Syndrome (ACS) with ST segment elevation myocardial infarction (STEMI) were very few, at the time of starting of this study. Keeping this in mind present study was conducted to compare the efficacy and safety of Aspirin alone with combination of aspirin plus Clopidogrel in prevention of events in Acute Coronary Syndrome with ST segment elevation myocardial infarction. Methods: Patients who are admitted to intensive coronary care unit within 12hrs after the onset of symptoms and whose diagnosis as ACS with ST segment elevation has been established were included in this study. Patients in group 1 received 325 mg of aspirin as loading dose, followed by 150 mg once daily. Patients in group 2 received a combination of aspirin and Clopidogrel 325 and 300 mg, respectively, as loading dose, followed by 150 mg of aspirin and 75 mg of Clopidogrel daily. All the patients received a fibrinolytic agent. Treatment response was weighed against the primary and secondary expected outcomes. Results: Addition of Clopidogrel to Aspirin resulted in significant reduction in severe ischaemia not requiring urgent revascularisation i.e.; 32% in Aspirin alone group versus 10% in Aspirin plus Clopidogrel group and recurrent angina with no ECG changes i.e.; 42% in aspirin alone group versus 20% in Aspirin plus Clopidogrel group. Similarly, there was an improvement in ejection fraction at the end of one month i.e.; 0.3% in Aspirin alone group versus 1.85% in Aspirin plus Clopidogrel group. Conclusions: This study demonstrates the benefit of adding Clopidogrel to Aspirin for myocardial infarction with ST-segment elevation. Treatment with a loading dose of 300mg of Clopidogrel followed by a daily dose of 75mg, in addition to aspirin, resulted in significant improvement in the secondary efficacy related outcomes in patients with acute coronary syndrome with ST-segment elevation.